LCL filter design for grid-connected single-phase flyback microinverter: a step by step guide - Muhamad Faizal Yaakub; Mohd Amran Mohd Radzi; Maaspaliza Azri; Faridah Hanim Mohd Noh (Institute of Advanced Engineering and Science, 2021)
Recently, LCL has become amongst the most attractive filter used for grid-connected flyback inverters. Nonetheless, the switching of power devices in the inverter configuration creates harmonics that affect the end application behavior and might shorten its lifetime. Furthermore, the resonance frequencies produced by the LCL network contribute to the system instability. This paper proposes a step-by-step guide to designing an LCL filter by considering several key aspects such as the resonance frequency and maximum current ripple. A single-phase grid-connected flyback microinverter with an LCL filter was designed then constructed in the MATLAB/Simulink environment. Several different parameter variations and damping solutions were used to analyze the performance of the circuit. The simulation result shows a promising total harmonic distortion (THD) value below 5% and harmonic suppression up to 14%.